2020
DOI: 10.1108/cg-11-2019-0335
|View full text |Cite
|
Sign up to set email alerts
|

CSR performance and the cost of debt: does audit quality matter?

Abstract: Purpose This study aims to shed light on the effect of corporate social responsibility (CSR) on the cost of debt. It also investigates whether audit quality affects the cost of debt incurred by socially responsible firms. Design/methodology/approach Based on a sample of French non-financial companies over the period 2005 to 2016, this paper uses panel data regressions. This paper re-estimates the model using Newey-West standard errors and the weighted-least-squares method. For further robustness, this paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 103 publications
(141 reference statements)
5
35
0
2
Order By: Relevance
“…Other studies revealed a positive relation between CSR performance and cost of debt, demonstrating that CSR is not a value driver with an impact on the firm's risk profile (e.g., Magnanelli and Izzo, 2017). Therefore, it seems that there is no unanimous consensus in the literature regarding the relationship between CSR and the cost of debt, and this link is still an empirical issue (Bacha et al, 2021). Debate and controversy continue thus to exist about how (i.e.…”
Section: Prior Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies revealed a positive relation between CSR performance and cost of debt, demonstrating that CSR is not a value driver with an impact on the firm's risk profile (e.g., Magnanelli and Izzo, 2017). Therefore, it seems that there is no unanimous consensus in the literature regarding the relationship between CSR and the cost of debt, and this link is still an empirical issue (Bacha et al, 2021). Debate and controversy continue thus to exist about how (i.e.…”
Section: Prior Researchmentioning
confidence: 99%
“…This could affect the financial uncertainty, leading to a higher risk and thus higher cost of debt financing. Many other authors also suppose that CSR can increase reputation and decrease the firm risks (Desender et al, 2020;Bacha et al, 2021). It seems therefore that corporate reputation, among other factors, might explain the mechanism by which CSR influences cost of debt.…”
Section: Prior Researchmentioning
confidence: 99%
“…This result suggests that the marketplace is becoming increasingly annoyed with regards to non-financial information, which shows that the disclosure of this fact can bring competitive blessings. In the context of the determinants of performance, Garcia et al [12] stipulate that ED is prominent for international companies involved in social obligation and sustainability practices. Thus, given the extant findings, we assume an association between the companies' ED and its market value.…”
Section: Hypothesis Development (H1): Ed and Fpmentioning
confidence: 99%
“…Thus, several theories can explain the relationship between the goals of companies and society. Inside the view of the scope of application of legitimacy theory and signal theory, the company's social responsibility has the capability to boom the overvaluation of the stock market value of the corporation [12].…”
Section: Hypothesis 2b (H2b)mentioning
confidence: 99%
“…In our study, we highlight how employee mistreatment deteriorates a firm's reputation in capital markets. Effective stakeholder treatment is related to greater transparency (Bacha et al, 2021;Mattingly et al, 2009;Sorensen and Miller, 2017). However, frequently sued firms may fail to convey trustworthiness and integrity.…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%